Fast Residual Quad-Tree Coding for the Emerging High Efficiency Video Coding Standard - Yongfei, Zhang; Zhe, Li; Mingfei, Zhao; Bo, Li (China communications, 2013)
In High Efficiency Video Coding, the Residual Quad-Yree （RQT） coding is used to encode the prediction residual for both intra and inter Coding Units （CU） and provides improved coding gains. However, this results in much higher computational complexities. To address this problem, we develop two fast RQT algorithms for intra- and inter-prediction residual coding respectively. For intra coding, the proposed algorithm selects the best prediction mode in the rate distortion mode decision process using a Prediction Unit （PU） size-dependent fast RQT depth decision on a reduced prediction mode candidates set from the rough mode decision process. For inter coding, in addition to CU size-dependent fast RQT depth decisions, we propose a discriminant analy- sis-based fast depth decision algorithm to det- ermine the best transform unit size. Experimental results show that on average, we can real- ise a 21.29% encoding time saving and 0.03% bit-rate reduction for intra coding, while 15% of the encoding time can be saved with a negligible coding performance loss for inter coding.